Intravascular lithotripsy (IVL) enabled the percutaneous closure of a severely calcified paravalvular leak regurgitation following implantation of a self-expandable transcatheter aortic valve: a case report - Evola, Salvatore; D’Agostino, Alessandro; Adorno, Daniele; Triolo, Oreste Fabio; Giarratana, Gioacchino; Castrovinci, Sebastiano; Argano, Vincenzo; Onorato, Eustaquio Maria (Frontiers in Cardiovascular Medicine, 2024)
Background: Paravalvular leak (PVL) regurgitation closure after self-expandable (SE) transcatheter aortic valve implantation (TAVI) can be more demanding than after balloon-expandable (BE) valve. Case Summary: An 85-year-old female suffering from long-standing atrial fibrillation and severe symptomatic aortic stenosis underwent SE TAVI (26 mm Evolut™ R®, Medtronic Inc., MN, USA). Eighteen months after TAVI she was admitted for congestive heart failure and two-dimensional (2D) transesophageal echocardiography (TEE) color Doppler showed moderate-severe PVL regurgitation through a long heavily calcified leak located underneath the left coronary sinus. Due to prohibitive surgical risk, a catheter-based PVL closure procedure was planned. A hydrophilic Terumo guide wire 0.35 inch-260 cm from right radial artery was then successfully advanced across the leak to the left ventricle (LV); however, among most of the catheters used, only a Glidecath 4-Fr could cross the leak over the hydrophilic wire. The hydrophilic guidewire was replaced with a stiffer guidewire that, after creating a loop in the LV, was advanced across the self-expandable valve into the descending aorta where it was snared and externalized through the left femoral artery, thus creating an arterioarterial (AA) loop. Over the exchange wire a 6-Fr Multipurpose guiding catheter was advanced and the leak was crossed with an additional 0.0014 coronary guidewire (PILOT, Abbott Vascular), predilated with two non-compliant balloon dilatation catheters to engage finally the PVL with the Shockwave balloon 3.0 mm × 12 mm (Shockwave Medical Inc, Santa Clara, California, USA). Intravascular lithotripsy (IVL) application for this highly calcified leak and the stronger support by stiff guidewire finally allowed progression of the 6-Fr dedicated delivery sheath (ODS III) into the LV. A 5 mm square twist (ST) device (PLD, Occlutech, Helsingborg, Sweden) was successfully deployed inside the leak and the final echocardiographic and angiographic control confirmed the effective PVL closure.In patients at high surgical risk with moderate-severe regurgitation post-SE TAVI through hard-toapproach calcified long tract, an extra support via AA loop is mandatory during PVL percutaneous closure. Furthermore, IVL application greatly facilitates progression of delivery sheath and occluder turning out to be key for successful procedure.